Village Development Sustainability Analysis: A Case Study in Cijeruk, Bogor Regency - Mujio; Rindiani Agustina Rahayu; Novida Waskitaningsih; Edy Mulyadi (Pusbindiklatren Bappenas, 2023)
Having abundant natural resources, the village is the foundation of the city. Villages have the potential to develop various natural, physical, social, demographic, and cultural resources that have not been optimally utilized. Therefore, sustainable village development is necessary to improve villagers' welfare and quality of life. This study aims to identify the status of village sustainability and sensitive attributes in village development through a case study in Cijeruk Village, Cijeruk District, Bogor Regency. The study examined four aspects of sustainability, ecology, economy, socio-culture, and legal and institutional dimensions using a Multidimensional Scaling (MDS) analysis called Rap-BUSAJI (Rapid Appraisal of Cijeruk Village Development). The study found that Cijeruk Village has a relatively sustainable status, with an overall index of 53.29%. The study also identified ten sensitive attributes that could be used to evaluate development. These ten attributes include three ecological dimension attributes (clean water sources for communal MCK, availability of clean water, and availability of MCK in every house); 3 attributes of the economic dimension (marketing range of main commodities, types of main commodities, and availability of supporting industries for main commodities); 3 attributes of the socio-cultural dimension (average community education level, number of agricultural workforces, and number of unemployment); and one attribute of legal and institutional dimensions (maps of disaster-prone areas availability).